Associations of timing of food intake with energy intake, eating behaviour traits and psychosocial factors in adults with overweight and obesity - Jacob, Raphaëlle; Tremblay, Angelo; Provencher, Véronique; Panahi, Shirin; Mathieu, Marie-Ève; Drapeau, Vicky (Frontiers in Nutrition, 2023)
Introduction: Whether a late distribution of food intake impacts obesity through increased energy intake remains uncertain and the behavioral characterization of late eating needs to be further investigated. The first objective of this study was to assess the associations between late eating and body mass index (BMI) and total energy intake (TEI), and whether TEI mediates the association between late eating and BMI. The second objective was to assess the associations between late eating and eating behavior traits or psychosocial factors and whether eating behaviors mediate the association between late eating and TEI. Methods: Baseline data from 301 individuals (56% women, age=38.7±8.5 years; BMI=33.2±3.4 kg/m2), who participated in four weight loss studies were used in this cross-sectional study. Total energy intake was assessed using a three-day food record from which the percentage of TEI after 17:00 and after 20:00 was calculated. Eating behavior traits and psychosocial factors were assessed with questionnaires. Pearson correlations and mediation analyses adjusted for age, sex, underreporting of energy intake, sleep duration and bedtime were performed. Results: Percent TEI after 17:00 and after 20:00 were associated with TEI (r=0.13, p=0.03 for both), and TEI mediated the association between percent TEI after 17:00 and BMI (β=0.01±0.01, 95% CI: 0.001, 0.02). Percent TEI after 17:00 was associated with disinhibition (r=0.13, p=0.03) and percent TEI after 20:00 was associated with susceptibility to hunger (r=0.13, p=0.03), stress (r=0.24, p=0.002) and anxiety (r=0.28, p=0.0004). In women, disinhibition mediated the association between percent TEI after 17:00 and TEI (β=3.41±1.43, 95% CI: 0.92, 6.47). Susceptibility to hunger mediated the association between percent TEI after 20:00 and TEI (β=0.96±0.59, 95% CI: 0.02, 2.34) in men and women. Conclusions: Late eating is associated with TEI and suboptimal eating behaviors which could contribute to explaining the association between timing of food intake and obesity.